Reaching for the Moon : the autobiography of NASA mathematician Katherine Johnson. - Johnson, Katherine G (Atheneum Books for Young Readers, 2019)
"The inspiring autobiography of NASA mathematician Katherine Johnson, who helped launch Apollo 11."--